Role of Mycobactin in the Growth and Virulence of Tubercle Bacilli - Golden, Carole A. (1974)
Tubercle bacilli failed to grow in iron-void media enriched with solutions of iron-containing transferrin (Tr) or ferritin (F) because these substances do not provide the bacilli with iron, which is essential for their growth. Animal serum and macrophages possessed no iron carrier with an ability to satisfy the need of the bacteria for the metal. Mycobactin (M), the growth-product of tubercle bacilli, removed iron from Tr and F and supplied the metal for bacillary utilization. The role of M in the growth of tubercle bacilli was influenced by nonionic surfactants which inhibited bacillary growth by removing M from the bacillary cells and interfering with the absorption of M-iron complexes. Experiments with Tween 80, Triton WR-1339, and lecithin showed that avirulent bacilli lose M at lower concentrations of the surfactants than virulent bacilli. Since avirulent and virulent bacilli possess the same amount of M, these findings indicate that M is bound more firmly to lipid-rich virulent than lipid-poor avirulent cells. These findings indicate that the resistance of virulent bacilli to the M-removing activity of the surfactants is an indicator of their ability to multiply in the infected host and may be used as a measure of bacillary virulence.